A major increase in oocyte cryopreservation cycles in the USA, Australia and New Zealand since 2010 is highlighted by younger women but a need for standardized data collection. Issue 3 (24th December 2020) - Johnston, Molly; Richings, Nadine M; Leung, Angela; Sakkas, Denny; Catt, Sally
Abstract: STUDY QUESTION: What are the cohort trends of women undergoing oocyte cryopreservation (OC)? SUMMARY ANSWER: There has been a dramatic increase in OC cycles undertaken each year since 2010, and the demographics of women accessing OC has shifted to a younger age group, but so far very few women have returned to use their cryopreserved oocytes in treatments. WHAT IS KNOWN ALREADY: Although OC, as a method of fertility preservation, is offered around the world, global data are lacking on who is accessing OC, who is returning to thaw oocytes and whether these trends are changing. STUDY DESIGN, SIZE, DURATION: A trinational retrospective cohort study was performed of 31 191 OC cycles and 972 oocyte thaw (OT) cycles undertaken in the USA (2010–2016) and 3673 OC and 517 OT cycles undertaken in Australia/New Zealand (Aus/NZ; 2010–2015). PARTICIPANTS/MATERIALS, SETTING, METHODS: Data were obtained from the USA Society for Assisted Reproductive Technology (SART) national registry and the Australian and New Zealand Assisted Reproduction Database (ANZARD). De-identified data were requested on all autologous oocyte freeze-all cycles and all cycles where autologous oocytes were thawed to be used in a treatment cycle for the time periods of interest. MAIN RESULTS AND THE ROLE OF CHANCE: In both the USA and Aus/NZ, there has been a dramatic rise in the number of OC cycles performed each year (+880% in the USA from 2010 to 2016 and +311% in Aus/NZ from 2010 to 2015). Across both regions, most women undergoing OC were aged in their late 30s, but the average age decreased over time (USA: 36.7 years vs 34.7 years in 2010 and 2016, respectively). The number of women returning for thaw cycles was low (USA: 413 in 2016, Aus/NZ: 141 in 2015) and most thaw cycles (47%) across both regions involved oocytes that were frozen for <6 months. In the USA, a higher proportion of cycles resulted in a live birth when only thawed oocytes were used, compared to cycles that combined thawed oocytes with fresh oocytes (25% vs 11%, respectively; P  < 0.001). Age at retrieval influenced live birth rate in the USA; 38% of thaw cycles started in women who stored oocytes when aged ≤35 years resulted in a live birth, whereas only 16% resulted in a live birth for women who stored oocytes when aged ≥36 years. Similar data were unobtainable from Aus/NZ. LIMITATIONS, REASONS FOR CAUTION: There were limitations associated with both the SART and ANZARD data outputs received. The format in which the ANZARD data were provided, and the inconsistencies seen amongst cycle reporting in the SART dataset, restricted data interpretation. For example, both datasets did not provide a clear indication as to why women were undergoing OC and it was not possible to accurately calculate duration of storage for thaw cycles in the USA. We also did not obtain details on embryo quality from either database and acknowledge that embryo quality and subsequent outcome (embryo freezing or discard) would be of interest, especially when considering the efficacy of OC. WIDER IMPLICATIONS OF THE FINDINGS: The data show that there is widespread demand for OC, and it is increasingly undertaken by younger women; however, the limitations encountered in the dataset support the need for a shift to a more uniform approach to data collection and presentation by large databases, worldwide. STUDY FUNDING/COMPETING INTEREST(S): This study received funding from the Fertility Society of Australia to support the ANZARD data extraction. M.J. is supported by an Australian Government Research Training Program Scholarship stipend. The authors declare no competing interests. TRIAL REGISTRATION NUMBER: N/A.